Safety and Tolerability of Adjunctive Eslicarbazepine Acetate in Pediatric Patients (Aged 4-17 Years) With Focal Seizures. (March 2020) - Mintz, Mark; Pina-Garza, Jesus E.; Wolf, Steven M.; McGoldrick, Patricia E.; Józwiak, Sergiusz; Grinnell, Todd; Cantu, David; Costa, Raquel; Moreira, Joana; Li, Yan; Blum, David
Objective: To evaluate the safety and tolerability of adjunctive eslicarbazepine acetate (ESL) in pediatric patients (aged 4-17 years) with refractory focal seizures. Methods: Pooled safety data from patients aged 4-17 years in Study 208 (NCT01527513) and Study 305 (NCT00988156) were analyzed. Both were randomized, double-blind, placebo-controlled studies of ESL as adjunctive treatment in pediatric patients with refractory focal seizures receiving 1 or 2 antiepileptic drugs. Incidences of treatment-emergent adverse events (TEAEs), serious adverse events (SAEs), TEAEs leading to discontinuation, and TEAEs of special interest were evaluated. Results: The safety population comprised 362 patients (placebo, n = 160; ESL, n = 202). The overall incidence of TEAEs was similar between the ESL (67.8%) and placebo groups (65.6%), with no clear dose-response relationship. The most frequently reported TEAEs with ESL were headache, somnolence, vomiting, and diplopia. Overall incidences of SAEs and TEAEs leading to discontinuation were higher with ESL versus placebo (9.9% vs 5.0% and 5.9% vs 2.5%, respectively). The majority of SAEs with ESL occurred in Study 305. Two deaths were reported, 1 with ESL (0.5%) due to cluster seizures (resulting in herniation of the cerebellar tonsils) and 1 with placebo (0.6%) due to asphyxia. TEAEs related to allergic reaction, hyponatremia, hypothyroidism, cytopenia, seizure exacerbation, cognitive dysfunction, psychiatric disorders, or suicide occurred infrequently (<9%). Conclusion: Adjunctive ESL was generally well tolerated in children aged 4-17 years with focal seizures. The safety profile of ESL in children was comparable to that observed in adults.